Central serous chorioretinopathy in uveitis patients after corticosteroid therapy: a report of 6 cases - N. A. Skvortsova; I. Papasavvas; C. P. Herbort Jr (Российский офтальмологический журнал, 2021)
Purpose. To report central serous chorioretinopathy (CSCR) in uveitis patients.Material and methods. A retrospective chart review of uveitis patients seen in a time frame of 20 years at the Centre for Ophthalmic Specialised Care, Lausanne, Switzerland. The ophthalmic and systemic features are presented.Results. Out of 1793 uveitis patients followed at the Centre for Ophthalmic Specialised Care, 6 patients (0.3%) developed CSСR following corticosteroid therapy due to uveitis. The mean age of patients was 40 ± 13.4 years, disease incidence was not associated with gender. In all 6 patients’ clinical disease was unilateral but subclinical signs were present in all fellow eyes. The mean duration of corticosteroid therapy before CSCR had occurred was 4.95 ± 4.0 months. The mean best-corrected visual acuity at the moment of CSCR was 0.6 ± 0.26 and 0.8 ± 0.17 after discontinuation of corticosteroids. Neurosensory retinal detachment and pigment epithelium detachment were observed in 3 eyes, respectively. During fluorescein angiography (FA), focal dye leakage and areas of alteration of RPE were observed in 6 out of 10 eyes. Diffuse hyperfluorescence of choroidal vessels observed by ICGA was detected in all eyes.Conclusion. Central serous chorioretinopathy should be suspected when functional and morphological deterioration occurs in uveitis patients receiving corticosteroid therapy with no signs of inflammation reactivation. This complication is extremely rare but serious condition which needs a prompt tapering and discontinuing of corticosteroids.